PENDIDIKAN KELUARGA PERSPEKTIF HADIS NABI MUHAMMAD SAW - Nurhadi Nurhadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
Abstract: The most successful and highly deserving educational figure as a model in Islamic family education is Rasullullah peace be upon him. This study aims to determine the functions and responsibilities of the head of the family in educating family members according to the hadith of the Prophet Muhammad. This research research library research model uses two data, primary and secondary. The primary data is the book of hadith Nine (polar al-Tis'ah), the secondary data as a supporter, for example the book of sharah from the book. The technique of collecting data uses the Tharq al-Hadith method (method of finding hadith), with the analysis technique using the contents of the analysis. The result is that the Function and Responsibility of Husband Educating the Perspective of the Family of the Prophet Muhammad in the Polar Hadith of Al-Tis'ah, are: 1). Husband's Functions and Responsibilities in Educating Wives: Husband of Family Leaders, Obligation to Educate Families, Obligation to Educate Wives, Teaching Wives of the Qur'an, Teaching Mandatory Bathing, Teaching Prayers to Wives, Teaching Ways to Request Shopping (Living), Educating About Numbers of the Month , Educating Wives Firmly and Wisely, Obligation to Teach Morals to Wives, Obligation to Teach Al-Qur'an as Mahar, Inviting Wife to Pray Night and Educating Wives with Affection. 2). Functions and Responsibilities of Husbands as Parents in Educating Their Children: Both Parents are Leaders, Parental Advice to their Daughters, Teaching the Koran to Their Children, Marrying Widows to Investigate Their Children, Teaching Children to Read and Write , Teaching Azan, Teaching Prayers, Teaching Prayers to Teach Teaching Fasting, Educating Boys and Girls, Praying for Children, Teaching Sports, Teaching Skills. Keywords: Education, Family, Perspective, Hadith, Prophet. .